Benin : Staff Report for the 2002 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, and Requests for an Extension of the Poverty Reduction and Growth Facility Arrangement and for an Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Benin's 2002 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility (PRGF), and Requests for an Extension of the PRGF Arrangement and for an Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). Macroeconomic performance remained broadly in line with the objectives of the PRGF-supported program in 2001. All performance criteria and structural benchmarks for end-December 2001 were met, except the benchmark on the adoption of an action plan for the privatization of the state-controlled bank.